Mode of action of abscisic acid in triggering ethylene biosynthesis and softening during ripening in mango fruit - Zaharah, S.; Singh, Zora; Symons, G.; Reid, J. (Elsevier, 2013)
The role of abscisic acid (ABA) in triggering ethylene biosynthesis and ripening of mango fruit was investigated by applying ABA [S-(+)-cis,trans-abscisic acid] and an inhibitor of its biosynthesis [nordihydroguaiaretic acid (NDGA)]. Application of 1 mM ABA accelerated ethylene biosynthesis through promoting the activities of ethylene biosynthesis enzymes (1-aminocyclopropane-1-carboxylic acid synthase, ACS; 1-aminocyclopropane-1-carboxylic acid oxidase, ACO) and accumulation of 1-aminocyclopropane-1-carboxylic acid (ACC), enhanced fruit softening and activity of endopolygalacturonase and reduced pectin esterase activity in the pulp. The activities of ethylene biosynthesis and softening enzymes were significantly delayed and/or suppressed in the pulp of NDGA-treated fruit. The ABA-treated fruit had higher total sugars and sucrose as well as degradation of total organic acids, and citric and fumaric acids compared with NDGA treatment. These results suggest that ABA is involved in regulating mango fruit ripening and its effects are, at least in part, mediated by changes in ethylene production.